Decoding Phonological Hurdles: An In-depth Study of Alveolar and Velar-Alveolar Consonant Cluster Mispronunciations among SMA PERSADA Lampung Students - Ayu Wandira; Yanuarius Yanu Dharmawan (Cita konsultindo, 2026)
English, as a global language, is widely taught in Indonesia from elementary to high school. However, Indonesian learners often experience difficulties in mastering English pronunciation, particularly in producing consonant clusters, which are uncommon in Indonesian. This study investigates mispronunciations of velar and velar–alveolar consonant clusters occurring at the end of English words and identifies the causes of these errors.The study employed audio recordings as the primary data collection method. Five senior high school students from Persada Senior High School, Bandar Lampung, whose first language is Indonesian, participated in the research. The participants were asked to read sentence-based materials taken from their English learning modules. Data were collected over three meetings, resulting in 250 pronunciation tokens (5 respondents × 25 English words).The findings reveal frequent pronunciation errors involving alveolar–alveolar and velar–alveolar consonant clusters in word-final positions. Two main types of errors were identified. The first is interlingual interference, where Indonesian phonological rules influence English pronunciation. This includes the deletion of final consonants in clusters (e.g., the omission of [d] in kind), devoicing of voiced consonants, the insertion of schwa [ə] between consonants, and consonant substitution to simplify articulation. The second type is intralingual error, which results from overgeneralization or improper combination of English pronunciation rules. These findings suggest that both native language interference and limited mastery of English phonological rules contribute to consonant cluster mispronunciation among Indonesian learners.